2022
DOI: 10.3390/su14148268
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors in MOOCs Adoption in Higher Education: A Meta-Analytic Path Analysis

Abstract: (1) Background: Due to the rapid growth of Massive Online Open Courses (MOOCs), higher educational institutions across the world are investing heavily in MOOCs to support their traditional teaching, their students’ learning experience, and their performance. However, the success of MOOCs highly depends on several factors that influence their success in higher education. Prior studies have attempted to investigate and predict user acceptance of MOOCs in higher education by using a variety of theoretical viewpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…Indeed, MOOCs offer an open online course experience that allows participants from different countries to join universities around the world [46]. Due to the rapid growth of MOOCs, colleges and universities across the country are investing heavily in MOOCs to support teaching and learning processes, provide learning experiences, and improve student performance [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, MOOCs offer an open online course experience that allows participants from different countries to join universities around the world [46]. Due to the rapid growth of MOOCs, colleges and universities across the country are investing heavily in MOOCs to support teaching and learning processes, provide learning experiences, and improve student performance [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…4. First, in the red cluster (n=14), there is a clear collaboration between Russian Federation (with 120 publications and 23 TLS) and Belgium (27,25); second, in the green cluster (n=12), we see the collaboration between Spain (216, 137), France (49,48), and Mexico (29,18). Germany, Taiwan, and Switzerland belong to the blue cluster (n=10).…”
Section: G Co-authorship For Authors and Countriesmentioning
confidence: 98%
“…Besides that, despite being the best model to explain user acceptance (Zaremohzzabieh et al, 2022;Chen & Zhao, 2022;Sohn & Kwon, 2020), UTAUT also has its shortcomings such as rather than the private space, UTAUT model originally formed for user acceptance of technology in the work environment (Baum et al, 2022) which cause it to be missing individual perceptions such as perceived usefulness and perceived ease of use constructs. Secondly, Venkatesh et al, (2003) suggested that extended constructs to be added in the original UTAUT model for further research in order to cater to the limitations of the original UTAUT model and to get a more comprehensive understanding of technology adoption and usage behavior.…”
Section: Limitation Of Studymentioning
confidence: 99%
“…Numerous studies ( Dalipi et al, 2018 ; Goopio and Cheung, 2021 ; Ghai and Tandon, 2022 ; Zaremohzzabieh et al, 2022 ) have been undertaken to determine the causes of attrition and lowering of retention rates in the case of MOOCs and for possible solutions. Moreover, Previous studies ( Watted and Barak, 2018 ; Abdullatif and Velázquez-Iturbide, 2020 ; Maya-Jariego et al, 2020 ; Chaveesuk et al, 2022 ) focused on a certain type of motivation in relation to MOOCs dropout.…”
Section: Introductionmentioning
confidence: 99%